NEDE: An open-source scripting suite for developing experiments in 3D virtual environments - Jangraw, David C.; Johri, Ansh; Gribetz, Meron; Sajda, Paul (Journal of neuroscience methods, 2014)
[Display omitted] •We present a design environment for developing realistic 3D experiments.•Subjects can explore custom virtual environments in search of randomized stimuli.•Leverages rendering power and community support of popular 3D game engine.•Interfaces with an eye tracker in real-time and syncs with an EEG system.•Simple runtime GUI controls task prompts, eye tracker calibration, and navigation. As neuroscientists endeavor to understand the brain's response to ecologically valid scenarios, many are leaving behind hyper-controlled paradigms in favor of more realistic ones. This movement has made the use of 3D rendering software an increasingly compelling option. However, mastering such software and scripting rigorous experiments requires a daunting amount of time and effort. To reduce these startup costs and make virtual environment studies more accessible to researchers, we demonstrate a naturalistic experimental design environment (NEDE) that allows experimenters to present realistic virtual stimuli while still providing tight control over the subject's experience. NEDE is a suite of open-source scripts built on the widely used Unity3D game development software, giving experimenters access to powerful rendering tools while interfacing with eye tracking and EEG, randomizing stimuli, and providing custom task prompts. Researchers using NEDE can present a dynamic 3D virtual environment in which randomized stimulus objects can be placed, allowing subjects to explore in search of these objects. NEDE interfaces with a research-grade eye tracker in real-time to maintain precise timing records and sync with EEG or other recording modalities. Python offers an alternative for experienced programmers who feel comfortable mastering and integrating the various toolboxes available. NEDE combines many of these capabilities with an easy-to-use interface and, through Unity's extensive user base, a much more substantial body of assets and tutorials. Our flexible, open-source experimental design system lowers the barrier to entry for neuroscientists interested in developing experiments in realistic virtual environments.